Genome-wide identification and expression analysis of serine hydroxymethyltransferase (SHMT) gene family in tomato (Solanum lycopersicum) - Liu, Zesheng; Pan, Xuejuan; Wang, Chunlei; Yun, Fahong; Huang, Dengjing; Yao, Yandong; Gao, Rong; Ye, Fujin; Liu, Xingjuan; Liao, Weibiao (PeerJ, 2022)
Serine hydroxymethyltransferase (SHMT) is one of the most important enzyme families in one-carbon metabolic pathway and photorespiration within plant cells. Recently studies reported the active roles of plant SHMTs in defending abiotic stresses. However, genome-scale analysis of SHMT in tomato is currently unknown. In this study, seven SHMT genes were identified in the tomato genome using a genome-wide search approach. In addition, their physicochemical properties, protein secondary structure, subcellular localization, gene structure, conserved motifs, phylogenetic and collinear relationships were analyzed. Our results demonstrated that tomato SHMT members were divided into two group and four subgroups, and they were conserved with the orthologs of other plants. Analysis of cis-acting elements showed that each of the SlSHMT genes contained different kinds of hormones and stress-related cis-acting elements in their promoter regions. Finally, qRT-PCR analysis indicated that SlSHMTs were expressed at different levels in different tissues, and they responded to UV, cold, heat, NaCl, H2O2, ABA and PEG treatments. These results provided definite evidence that SlSHMTs might involve in growth, development and stress responses in tomato, which laid a foundation for future functional studies of SlSHMTs.
Keywords: Tomato; SHMT; Gene family; Photorespiration; Expression analysis; Abiotic stresses alleviation